2010
DOI: 10.1002/jssc.201000627
|View full text |Cite
|
Sign up to set email alerts
|

New approaches of LC‐MS compatible method development on α1‐acid glycoprotein‐based stationary phase for resolution of enantiomers by HPLC

Abstract: Protein-based chiral stationary phases, in particular α(1)-acid glycoprotein, are chromatographic materials with a very broad application range. The chiral recognition ability of this selector allows the resolution of more than 90% of the molecules tested. A step-by-step description of the screening approach that we have developed is described in this article with two objectives in mind: obtaining a high success rate with a straightforward methodology that can be generally applied and allowing LC-MS compatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…48 The analysis was found to be relatively rapid and was also employed in the measurement of the enzyme catalytic activity in the incubation of D,L-amino acids with D-amino acid oxidase and the study of the enzyme kinetics. A generalized method development screening procedure that allows LC-MS compatibility was reported by Michishita et al 49 Applications developed using protein based CSPs included enantioseparations of doxazosin on an ovomucoid column, 50 dorzolamide hydrochloride on α-1-acid glycoprotein CSP, 51 and aryloxyphenoxypropionic herbicides in soil on α-1-acid glycoprotein CSP. 52 Miscellaneous.…”
Section: ' High Performance Liquid Chromatographymentioning
confidence: 99%
“…48 The analysis was found to be relatively rapid and was also employed in the measurement of the enzyme catalytic activity in the incubation of D,L-amino acids with D-amino acid oxidase and the study of the enzyme kinetics. A generalized method development screening procedure that allows LC-MS compatibility was reported by Michishita et al 49 Applications developed using protein based CSPs included enantioseparations of doxazosin on an ovomucoid column, 50 dorzolamide hydrochloride on α-1-acid glycoprotein CSP, 51 and aryloxyphenoxypropionic herbicides in soil on α-1-acid glycoprotein CSP. 52 Miscellaneous.…”
Section: ' High Performance Liquid Chromatographymentioning
confidence: 99%
“…In the case of human AAG (HAAG) it has been concluded that PTZ derivatives bind preferentially to only one common binding site, where hydrophobic forces are mainly involved, although electrostatic interactions also participate . The affinity of PTZs for HAAG has been employed for the development of glycoprotein‐based stationary phases for the resolution of enantiomers by HPLC .…”
Section: Introductionmentioning
confidence: 99%
“…HPLC‐MS/MS has become a popular analytical technique in the chiral analysis as it allows selective and sensitive measurement or identification of the compounds in synthetic sample mixtures or complex biological extracts [37–39]. The use of normal‐phase solvents, such as n ‐hexane in the mobile phase, cannot be accepted by atmospheric pressure chemical ionization and ESI interfaces connecting HPLC to MS, because the high proportion of n ‐hexane are generally incompatible with the atmospheric pressure chemical ionization or ESI source and also might raise a concern of an explosion hazard at an elevated temperature in the presence of a corona discharge or the high voltage of the electrospray needle [40,41]. Consequently, considering the MS‐compatibility and broader applicability, the reversed mode was used herein.…”
Section: Resultsmentioning
confidence: 99%